Evaluation of high-density polyethylene pipe installed using horizontal directional drilling. - Colwell, Donald A.
This paper presents the results of field installations of high-density polyethylene (HDPE) using the horizontal directional drilling process. One each of 114 mm (4 in.) diameter standard dimension ratio (SDR) 17 HDPE pipe, 219 mm (8 in.) diameter SDR 17HDPE pipe, and 324 mm (12 in.) diameter SDR 17 HDPE pipe were installed in a cohessionless soil medium. Various testing parameters were captured during the pullback phase of these three installations. Thses testing parameters considered of utilizing pressure transducers to capture the pullback and rotational pressures on the drilling rig, installing linear potentiometers inside the HDPE pipe to measure the axial strain on the pipe, and applying an external load cell to quantify the loading on the pipe during the pullback phase. Comparisons of the pullback and rotational pressure on the drilling rig, loading on the HDPE pipe, and average and maximum strain experienced by the HDPE pipe are presented with respect to the installed pipe diameter.
Keywords: Drilling; Pipes; Installation